The Practice of Pawning Rice Fields in Palembayan: Social Impacts and an Islamic Legal Perspective - Wiguna, Adek Indra; Makruf, Ali (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The implementation of pawning in the Minangkabau traditional tradition is a loan agreement by providing collateral to the borrower, as long as the debt has not been paid, the collateral will remain in the hands of the borrower and the benefits will also be taken, before Islam came, this pawning tradition had been carried out from generation to generation and became a custom for the indigenous people of Minangkabau.This study aims to describe the practice of pawning rice fields, to explain social relations, and to clarify the legal status of pawning rice fields in Palembayan District. The research method used in this study is a qualitative method. In qualitative research, the researcher is involved in the situation andsetting the phenomenon being studied. Researchers will always focus their attention on the reality or events in the context being studied. This research aims to explain the practice ofpawning, social impact and Islamic law review. This research employed a descriptive method with an analytical approach, analyzed qualitatively. Data were collected through fieldwork, interviews with community and religious leaders, and literature review. The analysis revealed that the practice of pawning rice fields among the Palembayan community does not comply with Islamic law. These findings can serve as baseline data for future researchers examining the problem in different contexts and on different issues.